Transformasi Pendidikan Jiwa Ibnu Sina: Menjawab Tantangan Era Digital - Fitria, Nur Annisa; Huriyah, Lilik (Institut Kariman Wirayudha Sumenep, 2024)
This research aims to examine Ibn Sina’s thoughts on how to face the challenges of the digital era in terms of mental education. The method in this research uses character research with library research in the form of descriptive data. The result of this research show that Ibn Sina’s intellectual history gave birth to various philosophical concepts, one of which is education in the soul. Then formulated so that it remains relevant in facing the dynamics of modern education by emphasizing the importance of balance between spiritual, moral and intellectual aspects in education. In the digital era, information is now abundant, and ethical challenges are increasingly complex, so the principles of mental education offered by Ibnu Sina can be used as a reference in forming ethical character and developing critical thinking skills. An emphasis on mental health and emotional balance is also an important focus, considering the negative impact social media can have on individuals. Through this research, the mental education proposed by Ibnu Sina has the potential to provide an effective solution for forming a generation that is not only academically intelligent, but also has strong human values.